SYNERGISTIC BRAKING: REAL-TIME INTEGRATION OF ANTI-LOCK AND MULTI-LEVEL REGENERATIVE BRAKING FOR ENCHANED SAFETY AND ENERGY EFFICIENCY - Ms B.Bhavani; Ms Patel Gauthami; Dr V Vijayasri Bolisetty; Dr U Yedukondalu (Utilitas Mathematica, 2025)
Regenerative braking and traditional braking systems, including hydraulic or anti-lock braking systems (ABS), are combined in the revolutionary Synergistic Braking System (SBS) to maximize performance, safety, and energy economy. In order to recover kinetic energy during slowdown and transform it into electrical energy that can be stored in batteries for later use, this system makes use of the benefits of regenerative braking. By smoothly switching to or combining with ABS or friction-based braking systems, it simultaneously guarantees strong braking performance in high-demand situations, including emergency stops or slick conditions. Depending on variables such vehicle speed, road conditions, battery charge level, and driver input, the SBS dynamically modifies the allocation of braking force between conventional and regenerative brakes. This optimizes energy recovery without sacrificing stability or safety. By automatically applying friction brakes when necessary, it also lessens the drawbacks of regenerative braking, such as decreased efficiency at low speeds or when the battery is fully charged. The technology is especially pertinent to cars operating in varied terrain or weather conditions, as well as electric and hybrid vehicles, where energy economy is crucial. Simulations and experimental research show that SBS guarantees reduced stopping distances and better control in challenging situations while also greatly enhancing braking performance and prolonging battery life. This technology is an important step toward intelligent and sustainable automobile systems, supporting international efforts to improve roads and lower carbon emissions.